Optical beam injection methods as a tool for analysis of semiconductor structures - Domaradzki, Jarosław; Kaczmarek, Danuta (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Optical beam injection methods, such as an optical beam induced current (OBIC) one, have several advantages. Such methods enable a comprehensive analysis of photocurrent generated at the microregion of a semiconductor material or a device by focused light beam. In the paper, examples of applications of the OBIC method for : i) examination of the silicon p-i-n diodes used in a scanning electron microscope (SEM) as a detector and ii) localization of electrically active regions at the interface of the new transparent oxide semiconductor (TOS)–semiconductor structure have been outlined.
Optica Applicata, Vol. 35, 2005, nr 1, s. 129-137
Keywords: optyka; transparent semiconducting oxide; heterojunction; p-i-n diode; optical beam; induced current